Associations between emotions and performance in cross-country skiing competitions - Moen, F.; Myhre, K.; Sandbakk, O. (The Sport Journal, 2016)
This article looks at how emotions are associated with performance during cross-country skiing competitions among 10 senior Norwegian national level athletes. The results in this study show that there is a relatively similar emotional distribution pattern found among the athletes who are most satisfied with their performance compared to the less satisfied ones. However, the intensity in their emotions is different. The most satisfied athletes have higher intensity in their eudaimonic and hedonic emotions, while the negative emotions "sad" and "scared" are higher among the less satisfied athletes. The emotion "angry" is not significantly different between the two groups of athletes, and significantly higher in intensity compared to "sad" and "scared". The emotions in this study explain 53 % of the variance in subjective performance. The results are discussed in regard of applied implications and possible future research.